Marine parks for coastal cities: A concept for enhanced community well-being, prosperity and sustainable city living. (May 2019) - Pittman, S.J.; Rodwell, L.D.; Shellock, R.J.; Williams, M.; Attrill, M.J.; Bedford, J.; Curry, K.; Fletcher, S.; Gall, S.C.; Lowther, J.; McQuatters-Gollop, A.; Moseley, K.L.; et al.
Abstract: Coastal cities continue to experience rapid urbanisation and population growth worldwide, linked to the diverse economic and social benefits flowing from proximity to the sea. Growing concern over human impacts upon coastal waters and global strategic goals for healthier cities requires that coastal cities develop innovative ways to inspire and empower communities to embrace and cherish city seascapes. Coastal city communities have much to gain from a healthier relationship with the sea. This paper proposes a collaborative community-led marine park concept that celebrates a city's connection to the marine environment, enhances sustainable economic prosperity and enables communities to participate in activities that deepen understanding, value, care and enjoyment of the city seascape. A city marine park (CMP) is not a marine protected area because it does not have biodiversity and heritage protection or ecosystem governance as a primary goal and does not aim to restrict human activities. A CMP enables city communities to collaborate towards a shared vision of elevated status and value for the city seascape. A CMP considers socio-economic and geographical context, including land-sea connectivity, and is integrated within a coastal city's strategic urban planning. This paper highlights core themes of a CMP and the diverse and wide-ranging benefits from coordinated activities that better connect the city community with its seascape. If co-created by the coastal city community and civic leaders, a CMP will form an enduring spatial nexus for progress toward healthy cities addressing multiple interlinked global sustainable development goals. Highlights: Novel holistic community-centred concept of a marine park for coastal cities. Innovative blue urban social policy for enabling, empowering and deepening citizen relationship with the city seascape. Potential to address multiple interlinked sustainable development goals.